APPLICATION OF CHOICE OF LAW IN JOINT VENTURE AGREEMENT DISPUTES BASED ON POSITIVE LAW IN INDONESIA - Khairany Azahra; Achmad Rafi Al Khalish; Hawila Winona L; Rizki; Rousseau Jordan A; Estri Dewangga C J; Safarah Yardha (Zhata Institut, 2024)
A joint venture is one type of cooperation that is currently often carried out by companies. This term has been quite popular in recent years, along with the emergence of more startups and the scope as well. The agreement that forms the basis for the formation of a joint venture company is the joint venture agreement and articles of association. A joint venture agreement is an agreement between prospective shareholders of a joint venture company that is subject to the law of contract. Joint ventures are not only limited to the joint efforts of small companies, there are also joint ventures whose members are large-scale companies even from abroad, and the formation of a contract is based on applicable law. In the context of an international scale, an international contract is needed which is a contract in which there is a foreign element. What makes international contracts unique is the emergence of the main element called the element of freedom of the parties to make a choice of law. The choice of law against a national law of a particular country does not mean that the judicial body of that country is automatically authorized to resolve the dispute, but the implication of the choice of law on the resolution of disputes between international joint ventures is based on this choice, it is known which institutions and laws are used and have the authority to examine and adjudicate disputes arising from an international business contract to provide legal certainty.